3D Proximal Tubule Tissues Recapitulate Key Aspects of Renal Physiology to Enable Nephrotoxicity Testing - King, Shelby M.; Higgins, J. William; Nino, Celina R.; Smith, Timothy R.; Paffenroth, Elizabeth H.; Fairbairn, Casey E.; Docuyanan, Abigail; Shah, Vishal D.; Chen, Alice E.; Presnell, Sharon C.; Nguyen, Deborah G. (Frontiers in Physiology, 2017)
Due to its exposure to high concentrations of xenobiotics, the kidney proximal tubule is a primary site of nephrotoxicity and resulting attrition in the drug development pipeline. Current pre-clinical methods using 2D cell cultures and animal models are unable to fully recapitulate clinical drug responses due to limited in vitro functional lifespan, or species-specific differences. Using Organovo’s proprietary 3D bioprinting platform, we have developed a fully cellular human in vitro model of the proximal tubule interstitial interface comprising renal fibroblasts, endothelial cells, and primary human renal proximal tubule epithelial cells to enable more accurate prediction of tissue-level clinical outcomes. Histological characterization demonstrated formation of extensive microvascular networks supported by endogenous extracellular matrix deposition. The epithelial cells of the 3D proximal tubule tissues demonstrated tight junction formation and stable gamma glutamyl-transferase activity for at least 30 days in culture. Expression of renal uptake and efflux transporters was also sustained over 30 days, and polarized localization and function of P-gp and SGLT2 was confirmed. Treatment of 3D proximal tubule tissues with the nephrotoxin cisplatin induced loss of tissue viability and epithelial function in a dose-dependent fashion, and cimetidine rescued these effects, confirming the role of the OCT2 transporter in cisplatin-induced nephrotoxicity. Together, these results suggest that the bioprinted 3D proximal tubule model can serve as a test bed for the mechanistic assessment of human nephrotoxicity and the development of pathogenic states involving epithelial-interstitial interactions, making them an important adjunct to animal studies.